APPEARANCES OF HUMAN CREATIVE KNOWLEDGE - Saidahmatova Sadoqat Usmonjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, man’s ability to know is not limited, but not all the things and events that he wants to know in each specific historical period, but only knowing what he can know and knowing later what he does not know, that human knowledge has no limit, because the infinity of the macro-micro world is the limit of human knowledge. it is thought that it also shows infinity.